Minimal, encapsulated proteomic-sample processing applied to copy-number estimation in eukaryotic cells - Kulak, Nils A; Pichler, Garwin; Paron, Igor; Nagaraj, Nagarjuna; Mann, Matthias (Nature methods, 2014)
A streamlined, robust sample-preparation method for mass spectrometry–based proteome analysis is reported. All sample preparation steps are carried out in a single enclosed reactor, reducing the potential for contamination and losses, and enabling comprehensive proteome coverage. Mass spectrometry (MS)-based proteomics typically employs multistep sample-preparation workflows that are subject to sample contamination and loss. We report an in-StageTip method for performing sample processing, from cell lysis through elution of purified peptides, in a single, enclosed volume. This robust and scalable method largely eliminates contamination or loss. Peptides can be eluted in several fractions or in one step for single-run proteome analysis. In one day, we obtained the largest proteome coverage to date for budding and fission yeast, and found that protein copy numbers in these cells were highly correlated ( R 2 = 0.78). Applying the in-StageTip method to quadruplicate measurements of a human cell line, we obtained copy-number estimates for 9,667 human proteins and observed excellent quantitative reproducibility between replicates ( R 2 = 0.97). The in-StageTip method is straightforward and generally applicable in biological or clinical applications.